A review of botanical characteristics, chemical composition, pharmacological activity and use of parsley - Punoševac, Milka; Radović, Jelena; Leković, Aleksandra; Kundaković-Vasović, Tatjana (Archives of Pharmacy, 2021)
Parsley is a biennial aromatic plant from the Apiaceae family, which is characterized by an unbranched root, pinnately divided leaves, umbels and schizocarp. It contains essential oil in all parts, with phenylpropane and terpene compounds as main components. It is rich in flavonoids and other polyphenolic compounds, containing furanocoumarins, carotenoids, polyacetylenes, and its leaves are a source of vitamins and minerals. The chemical composition of parsley depends on a number of factors, so it differs not only in different parts and varieties of the plant, but also in different samples of the same parts of one variety. The most important parsley compounds are myristicin, apiol, 1-allyl-2,3,4,5-tetramethoxybenzene, β-phellandrene, 1,3,8-p-menthatriene, β-pinene, terpinolene, apiin, oxypeucedanin and falcarinol. Parsley has a long tradition of use in the treatment of urinary tract disorders, and modern in vitro and in vivo studies reveal numerous effects of various parsley preparations such as diuretic, antiurolithiasis, hypouricemic, hypolipidemic, hypoglycemic, hypotensive, antioxidant, anti-inflammatory and antiplatelet effect. Today, apart from its medical application, parsley is one of the most commonly used culinary herbs.